Numerical study of hydrodynamic conditions and sedimentary environments of the suspended kelp aquaculture area in Heini Bay. (5th January 2020) - Zhang, Zehua; Huang, Haijun; Liu, Yanxia; Bi, Haibo; Yan, Liwen
Abstract: Kelp aquaculture is one of the most important exploitation and utilization activities in coastal areas. The impacts of high-density kelp aquaculture on coastal area environments are attracting increasing attention. Based on in situ data from the suspended kelp aquaculture area of Heini Bay, numerical simulations were applied to distinguish hydrodynamic and sediment transport features under natural and aquaculture conditions. By comparing model simulations with observations, the calibrated models reflected the hydrodynamic conditions and sedimentary environments in Heini Bay well. Although the kelp scenario model was calibrated by data measured in an early stage of aquaculture and produced a relatively conservative result, the model was able to simulate the trend of sedimentary environment changes in the aquaculture area. The results of the simulations indicated that, after the occurrence of aquaculture activities, the average velocity was reduced by approximately 21% in the waters around Chu Island and Moye Island, and by 50% within the kelp aquaculture area. Along the western edges of the aquaculture area (i.e., the nearshore area), the average velocity barely changed, but the instantaneous velocity during the flood/ebb tide may increase by up to 3 times. The annual maximum erosion rate around Chu Island, Moye Island and Heishi Reef decreased by approximately 30%, and the total range of the erosion area where the erosion intensity was not less than 0.01 m/yr decreased by almost 36%. The deposition area in Heini Bay shifted to deeper waters, and almost the entire kelp aquaculture area was in a deposition state. However, the deposition rates in the aquaculture area were reduced accordingly. Highlights: Numerical simulations of the suspended kelp aquaculture area were established based on various in situ data. The hydrodynamic and sediment transport features under natural and aquaculture conditions were distinguished. The effects of suspended kelp aquaculture on the local hydrodynamic conditions and sedimentary environments were discussed.